2020
DOI: 10.1002/jhet.4165
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of some 1,3‐benzoxazol‐2(3H)‐one hybrid molecules as potential antioxidant and urease inhibitors

Abstract: A new series of 1,3‐benzoxazol‐2(3H)‐one hybrid compounds, including coumarin, isatin 1,3,4‐triazole and 1,3,4‐thiadiazole moieties, were synthesized and biologically evaluated for their antioxidant capacities and anti‐urease properties. The synthesized benzoxazole‐coumarin (6a–e) and benzoxazole‐isatin (10a–c) hybrids showed remarkable urease inhibitory activities with IC50 (μM), ranging from 0.0306 ± 0.0030 to 0.0402 ± 0.0030, while IC50 of standard thiourea is 0.5027 ± 0.0293. The synthesized benzoxazole‐tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Yilmaz and coauthors [99] synthesized new analogs of 1,3benzoxazol-2(3H)-one containing 1,3,4-triazole (36) and tested their urease inhibition potency (Canavalia ensiformis). Results found that all the screened derivatives exhibited superior potency (IC 50 = 0.0307-0.0367 μM) than the used standard; thiourea (IC 50 = 0.5027 μM).…”
Section: Chemistryselectmentioning
confidence: 99%
“…Yilmaz and coauthors [99] synthesized new analogs of 1,3benzoxazol-2(3H)-one containing 1,3,4-triazole (36) and tested their urease inhibition potency (Canavalia ensiformis). Results found that all the screened derivatives exhibited superior potency (IC 50 = 0.0307-0.0367 μM) than the used standard; thiourea (IC 50 = 0.5027 μM).…”
Section: Chemistryselectmentioning
confidence: 99%
“…The IC 50 values reported in many urease enzyme inhibition studies in the literature are close and similar to the results we have obtained. [12][13][14][15][16][20][21][22]…”
Section: Urease Inhibition Assay and Kinetic Parametersmentioning
confidence: 99%
“…According to recent studies, several quinazolinone derivatives with diverse side groups have anti-urease activity. [11][12][13][14][15][16] In our recent studies, we investigated quinazolinone derivatives, that were very active inhibitors of jack bean urease. However, there is still a considerable need for alternative or novel treatments of H. pylori associated with diseases.…”
Section: Introductionmentioning
confidence: 99%
“…These scaffolds have diverse biological properties including anticancer, 10 antioxidant, 11 antidepressant, 12 antimicrobial, 13 anti-nociceptive, 14 anti-asthmatic, 15 anti-inflammatory, 16 anti-pyretic, 17 antileishmanial, 18 anti-coagulant, 19 anti-tubercular, 20 antiviral, 21 antibacterial, 22 antifungal, 23 antimalarial, 24 antidiabetic, 25 anti-hepatitis C virus, 26 anti-HIV, 27 anti-proliferative, 28 antiplatelet, 29 and antiplasmodial 30 activities. They are also well-known inhibitors of urease, 31 acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), 32 cyclooxygenase (COX), 33 lipoxygenase (LOX), 34 monoamine oxidases A and B (MAO-A and MAO-B), 35 tubulin polymerization, 36 carbonic anhydrase, 37 α-glucosidase, 38 inositol-requiring enzyme 1 (IRE-1) RNase, 39 mitochondria-targeting antitumor STAT3, 40 selective cyclin-dependent kinase 9 (CDK9), 41 selective aldehyde dehydrogenase 1A1, 42 coagulation factor XIIa (FXIIa), 43 casein kinase 2 (CK2), 44 steroid sulfatase (STS), 45 chitin synthase (CHS), 46 etc. These heterocyclic scaffolds have antagonistic behavior against chemokine-like factor 1 (CKLF1), 47 G-protein-coupled receptor 35 (GPR35), 48 orphan G-protein-coupled receptor 55 (GPR55), 49 A 3 adenosine receptor, 50 and many others.…”
Section: Introductionmentioning
confidence: 99%